ANALISIS RASIO KEUANGAN TERHADAP LAPORAN KEUANGAN PT. MULIA BOGA RAYA,TBK. TAHUN 2023 - Suryatama Mahardika (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This article aims to find out the performance of PT. Mulia Boga Raya, Tbk in accordance with the company's financial statements for 2023 by analyzing liquidity ratios (current ratio and quick ratio), activity ratio (receivables turnover ratio, inventory turnover ratio, fixed asset turnover ratio and total asset turnover ratio), debt ratio (debt to assets ratio and debt to equity ratio) and profitability ratio (profit margin, return on equity, return on asset). The research method used is a qualitative descriptive method, namely by collecting, processing, analyzing and presenting data descriptively with a sample of financial statements of PT. Mulia Boga Raya, Tbk. for the 2023 financial year. The results of the research obtained that PT. Mulia Boga Raya, Tbk. in 2023 is a liquid company. This is evidenced by the company's performance through the analysis of liquidity ratios and activity ratios which shows that the company is able to pay off its short-term debts and is very efficient in carrying out its business operations and is able to convert its inventory into sales. Meanwhile, for the solvency ratio and profitability ratio of PT. Mulia Boga Raya, Tbk. in the 2023 financial year also showed a positive performance trend where the company has a good enough ability to fulfill its obligations, and is very effective in using its assets to generate profits, as well as efficient in managing operations and costs so that the company is able to generate very significant revenue and improve the company's financial capabilities by increasing equity or reducing debt